(untitled) - Nguyen, Thi Ngoc Tran (Can Tho, 2018)
This book introduce about Optimize EzRAD protocol in a new lab. Compare levels of genetic diversity and genetic difference between populations of M. siamensis in Hau and Tien Rivers and Paksan of Laos.
Keywords: Nuôi cá,Fish culture; Nghiên cứu,Research